HPA-1a/1b could be considered a molecular predictor of poor prognosis in chronic hepatitis C - Grotto, Rejane Maria Tommasini [UNESP]; Santos, Francielle Martins [UNESP]; Picelli, Natália [UNESP]; Silva, Giovanni Faria [UNESP]; Ferrasi, Adriana Camargo [UNESP]; Sarnighausen, Valéria Cristina Rodrigues [UNESP]; Pardini, Maria Inês de Moura Campos [UNESP] (FapUNIFESP (SciELO), 2019)
Introduction: HPA polymorphism has been associated with HCV presence and fibrosis progression in chronic hepatitis C. However, it is unknown if there is an association between HPA-1 polymorphism and hepatocellular carcinoma (HCC). Therefore, this study aimed to evaluate HPA-1 polymorphism in the presence of HCC. Methods: PCR-SSP was used to perform HPA genotyping on 76 HCV-infected patients. Results: There was no association between patients with and without HCC. There was significant difference in HPA-1 genotypic frequency distribution between HCC and F1/F2 fibrosis degree. Conclusions: The HPA-1a/1b polymorphism appears to be more associated with liver damage progression than with HCC presence.
Keywords: Hepatitis C virus; Hepatocellular carcinoma; Human platelets antigens